Local lattice distortion in NiCoCr, FeCoNiCr and FeCoNiCrMn concentrated alloys investigated by synchrotron X-ray diffraction. (5th October 2018) - Tong, Y.; Jin, K.; Bei, H.; Ko, J.Y.P.; Pagan, D.C.; Zhang, Y.; Zhang, F.X.
Highlights: Fine-grained fcc concentrated alloys with weak texture were prepared for lattice distortion characterization. Lattice distortion in NiCoCr, FeCoNiCr and FeCoNiCrMn concentrated alloys is quantitatively characterized for the first time. Lattice distortion in NiCoCr (0.23%) and FeCoNiCrMn (0.24%) is comparable, while negligible in FeCoNiCr (0.04%). Size mismatch is not the sole factor to induce lattice distortion in high-entropy alloys. Graphical abstract: Unlabelled Image Abstract: Severe lattice distortion is presumptively considered as a core effect of high-entropy alloys, but quantitative measurements are still missing. Here, we demonstrate that the lattice distortion in high-entropy alloys can be quantitatively analyzed based on pair distribution function obtained from synchrotron X-ray diffraction. By applying this method to equiatomic NiCoCr, FeCoNiCr and FeCoNiCrMn concentrated alloys, we found that the local lattice distortion in the NiCoCr (0.23%) and FeCoNiCrMn (0.24%) alloys are comparable while negligible in the FeCoNiCr alloy (0.04%). The origin of local lattice distortion in the NiCoCr and FeCoNiCrMn concentrated alloys was discussed.